Aspect Oriented Programming Tools for .Net Framework - Sarode, PR; Jugele, RN (International Journal of Computer Sciences and Engineering, 2019)
Aspect oriented programming is a young concept in Computer science. It is succeeding from research projects towards commercial applications. Most of the current AOP tools suitable for commercial projects are proposed for Java platform only, which bounds their applicability. AspectJ is the leading tool for Java technology, the only way to implement a new programming paradigm such as Aspect Oriented Programming is either to extend the Java language or to develop Java API to support it. For .NET, the situation is different — it is a multilanguage programming environment. Today, Aspect Oriented Programming is supported in most languages and platforms. For Microsoft .NET, PostSharp is the most advanced and mature framework, and has been used commercially for several years. There are various known Aspect Oriented Programming tools for Microsoft.NET also. This paper present the analysis and overview of the all various popular AOP tools for .Net framework in detail.